Anonimiteit en pseudonimiteit van Bybelse geskrifte - Lombard, H. (Hervormde teologiese studies, 1986)
Anonamity and pseudonymity of biblical writings Since ancient times authors presented their writing to the public under pseudonyms. Subsequently, authors also wrote anonomously. The literary phenomenon of pseudonymity creates the most substantial problems among literary critics, since all cultures and authors' conventions emphatically reject plagiarism and forgeries. An assessment of this literary technique should be conducted with reference to the motives and objectives behind the utilization of this technique.